Interacción en el aula y lenguaje: ¿cómo enfrentar su investigación? (2005)
This article refers to a reflection about the implications the recognition of the interaction and language relation has in analysis models of classroom interaction. For this purpose, at the beginning, there is a brief explanation about the way authors understand learning and teaching; later, interaction in the classroom is characterized as a particular social practice; then, it is intended to put in evidence the relation teaching-learning and language. In the fourth moment, there is a historical review about research approaches focused in this objective, followed by a reflection about some of the implications derived from methodological decisión making in agreement with conceptions presented in the first part. Finally, the article closes with some ideas which the authors hope help as a reflection for those interested in research in classroom interaction.